Confessions of a Hard-Hat Junkie: Reflections on the Construction of Anheuser-Busch Hall - Michael M. Greenfield (Washington University Law Quarterly, 1998)
In this Article I will describe the process by which the Washington University School of Law has come now to occupy Anheuser-Busch Hall. By doing so, I hope to provide some insight and assistance to those at other schools who face similar projects.
Keywords: Architecture -- Law & legislation; Law schools -- Missouri; Washington University. School of Law